EFEKTIVITAS LABORATORIUM BAHASA DALAM MENINGKATKAN KETERAMPILAN MENYIMAK (MAHARAH ISTIMA') SISWA MADRASAH ALIYAH - Abdullah, Abdullah; Junaidi, Ahmad Syafa'at; Mira, Mira (As-Sulthan Journal of Education, 2026)
This study aims to determine the effectiveness of using a language laboratory to improve Arabic listening skills (Maharah Istima') among students. The conventional teaching of listening skills often faces challenges due to the lack of engaging media, resulting in suboptimal student comprehension. This research employed a quantitative approach with a quasi-experimental design involving a pre-test and post-test control group. The research was conducted at Ma'had Darul Lughah wad Da'wah, Pasuruan, with a sample of 40 first-grade Aliyah students divided into an experimental group and a control group. Data were collected through observations, interviews, and tests, and then analyzed using the t-test formula. The findings revealed a significant difference between the two groups. The experimental group achieved a mean post-test score of 72 (categorized as Good), while the control group scored 59 (categorized as Poor). The t-test analysis showed that the t-count (5.37) was higher than the t-table (2.09) at a 5% significance level. Therefore, it is concluded that the use of a language laboratory is effective and significantly improves students' Arabic listening skills compared to conventional methods.